Ideological representation of violence and information packaging in Arabic headline news: a case study of the Al-Ahram Arabic daily newspaper - Anis, Muhammad Yunus (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Arabic language has a pattern of information packaging (Theme + Rheme) that is based on Systemic Functional Linguistics (SFL). This pattern is used as the model for deciphering the information structure in the Arabic headline news. This article investigates information packaging in the Arabic headline news. There are two basic items in information structure, namely (1) Theme (given information) and (2) Rheme (new information). The data used in this article are Arabic headline news from a number of Arabic daily newspapers. Theme has been defined as given information and Rheme is recognized as new information. Some Arabic headline news contains elements of physical and emotional violence. In order to discover the ideological representation of violence in Arabic news, the newspaper reader first needs to know and understand the pattern of information packaging used. The main aim of this research is to elaborate on two basic problems, they are: (1) Information packaging in headline news and (2) Ideological representation of violence in the Arabic mass media. This article also investigates the nature of violence in the Arabic Mass Media. The results of the analysis confirm that the system of Theme and Rheme is an effective tool for unlocking the information structure in Arabic headline news and detecting the underlying ideology of violence in the Arabic mass media.